2019
DOI: 10.7759/cureus.4292
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Depression Among Community Dwelling Healthy Elderly and the Predisposing Socio-environmental Factors

Abstract: Introduction The average life expectancy is increasing with better medical facilities and evolving technology. The ratio of the geriatric population is increasing, which drives a need to invest more in the physical and psychological health of older people. The aim of this study was to assess the incidence of depression in community-dwelling healthy older adults. Methods Geriatric Depression Scale-15 (GDS-15) was utilized in this study. Community-dwelling older adults (age 65+ y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In our study, older adults who were married had lower rates of depressive symptoms. Previous research on older adults has revealed that marital status was a strong predictor of depressive symptoms, with unmarried older adults being more likely to be depressed (6,37). Single or split older adults had higher levels of depressive symptoms (37).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study, older adults who were married had lower rates of depressive symptoms. Previous research on older adults has revealed that marital status was a strong predictor of depressive symptoms, with unmarried older adults being more likely to be depressed (6,37). Single or split older adults had higher levels of depressive symptoms (37).…”
Section: Discussionmentioning
confidence: 95%
“…Previous research on older adults has revealed that marital status was a strong predictor of depressive symptoms, with unmarried older adults being more likely to be depressed (6,37). Single or split older adults had higher levels of depressive symptoms (37). Older adults could be psychologically affected by these events.…”
Section: Discussionmentioning
confidence: 97%
“…In terms of marital status, our results suggested that older people who were not living with their spouses (separated/divorced/widowed/single) had relatively high odds of depressive symptoms. Similarly, many studies have reported that marital status is a key variable that affects depressive symptoms among the elderly population (Javed, 2014;Xie et al, 2010;Fatima et al, 2019). Kim and McKenry (2002) found that separation, divorce, and death of a spouse have significant effects on exacerbating depressive symptoms.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…The scale consists of 15 questions and is calculated by adding the scores of yes answers (1 point) with binary options of "yes" and "no." The score is based on 15 points in total; if the total score is ≥5, the individual is considered at risk of depression [8,21]. The tool's reliability had a Cronbach's alpha of 0.85.…”
Section: Depressionmentioning
confidence: 99%